2017
DOI: 10.3892/etm.2017.5139
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic therapy improves arterial endothelial function following non‑cardiovascular surgery: A randomized, placebo‑controlled trial

Abstract: Pain subsequent to non-cardiac surgery may affect the endothelial function, which in turn contributes to myocardial injury (MI). The present study examined whether effective pain control is able to improve the postoperative endothelial function. Patients (n=160) undergoing laparoscopic cholecystectomy were randomly assigned into two groups, treated with tramadol analgesic or saline (placebo) following surgery. On preoperative day 1 (baseline) and postoperatively at 2 h, 1 day and 5 days, pain was assessed on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The laparoscopic cholecystectomy (LC) has been considered as the golden standard for cholecystolithiasis in clinical practice; however, there were still many controversies over the treatment of choledocholithiasis. 9,10 Nowadays, open common bile duct exploration, laparoscopic common bile duct exploration, choledochoscopic common bile duct exploration, and endoscopic retrograde cholangiopancreatography (ERCP) (including endoscopic sphincterotomy [EST], endoscopic papillary balloon dilation [EPBD], and endoscopic nasobiliary drainage [ENBD]) are widely adopted in the treatment of choledocholithiasis. Usually, a multiple-method combination is adopted since a single method cannot completely clear the lithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…The laparoscopic cholecystectomy (LC) has been considered as the golden standard for cholecystolithiasis in clinical practice; however, there were still many controversies over the treatment of choledocholithiasis. 9,10 Nowadays, open common bile duct exploration, laparoscopic common bile duct exploration, choledochoscopic common bile duct exploration, and endoscopic retrograde cholangiopancreatography (ERCP) (including endoscopic sphincterotomy [EST], endoscopic papillary balloon dilation [EPBD], and endoscopic nasobiliary drainage [ENBD]) are widely adopted in the treatment of choledocholithiasis. Usually, a multiple-method combination is adopted since a single method cannot completely clear the lithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies in non‐cardiac surgery have shown that surgery causes a state of acute endothelial dysfunction lasting for days after the surgical procedure 3,4 . The extent of endothelial dysfunction after surgery seems to be influenced by perioperative factors such as type of surgery, anaesthetics and pain 3,5‐7 . While pre‐operative endothelial dysfunction has been associated with the risk of developing perioperative major adverse cardiovascular events 8‐10 the clinical consequences of endothelial dysfunction in the perioperative period remain to be established.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The extent of endothelial dysfunction after surgery seems to be influenced by perioperative factors such as type of surgery, anaesthetics and pain. 3,[5][6][7] While pre-operative endothelial dysfunction has been associated with the risk of developing perioperative major adverse cardiovascular events 8-10 the clinical consequences of endothelial dysfunction in the perioperative period remain to be established. Endothelial dysfunction early after surgery may play a role in the pathophysiology of myocardial injury.…”
mentioning
confidence: 99%